The Influence of Human Resource Competence, Community Management, and Local Government Support on the Sustainability of the Rompong Art Community in Banggai Regency - Riski Mahyudin Lamato; Muh. Yushar Mustafa (PT Smart Media Makassar, 2025)
This study is a quantitative study that aims to determine the influence of Human Resource Competence, Community Management, and Local Government Support on the Sustainability of the Rompong Art Community in Banggai Regency. The population in this study consists of all members of the Rompong Art Community who are still active as of 2024, totalling 250 people, comprising various branches of the arts such as theatre, traditional music, dance, visual arts, literature, photography, and multimedia. The sampling technique used purposive sampling with a sample size of 100 respondents, who were the heads of the Art Community from each branch of art. The research instrument used a Likert scale to measure the variables of Human Resource Competence (X₁), Community Management (X₂), Local Government Support (X₃), and Community Sustainability (Y). Data analysis was performed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS) version 25. The results showed that Human Resource Competence and Community Management had a positive and significant effect on Community Sustainability, while Local Government Support had no significant effect. Simultaneously, the three independent variables had a positive and significant effect on the Sustainability of Rompong Art Community in Banggai Regency. These findings illustrate that the sustainability of arts communities is greatly influenced by the quality of human resources and effective community management systems, while government support still needs to be improved in order to play a greater role in strengthening the existence of arts communities in the region.